Developing and Evaluating an ESRI Story Map as an Educational Tool. Issue 1 (19th July 2018) - Cope, M. P.; Mikhailova, E. A.; Post, C. J.; Schlautman, M. A.; Carbajales-Dale, P.
Abstract : Core Ideas: An ESRI Story Map (a web application based on maps) was developed and tested for teaching topography. Student evaluations of the ESRI Story Map were positive. ESRI Story Maps can be an effective teaching and learning tool. Environmental Systems Research Institute (ESRI) Story Maps are web applications based on maps and other multimedia, which can be effectively used in soil science education. The purpose of this study was to develop an ESRI Story Map "Soil Forming Factors: Topography" for teaching an introductory soil science courses and to assess the performance of the newly developed story map using ESRI's "five principles of effective storytelling" and user responses to a quiz testing the acquired knowledge. Specific learning objectives were stated on each story map page and throughout the learning materials. Navigation of each story map page is controlled by the participant via tabs to allow the user to control the pace of the learning experience. Participants received an average score of 8.2 (out of 9 maximum points) for the quiz. The ESRI Story Map scored well for each principle of the ESRI's five principles of effective storytelling, with more than 70% of responses having an excellent rating. Additional comments suggest that participants were positive about the ESRI Story Map as a stand‐alone teaching tool or in combination with PowerPoint slides. The ESRI Story Map "Soil Forming Factors: Topography" can be further improved by incorporating interactive exercises. ESRI Story Maps can be effective teaching tools in science education.